Protective anti-tumor vaccination against glioblastoma expressing the MHC class II transactivator CIITA - Celesti, Fabrizio; Gatta, Andrea; Shallak, Mariam; Chiaravalli, Anna Maria; Cerati, Michele; Sessa, Fausto; Accolla, Roberto S.; Forlani, Greta (Frontiers in Immunology, 2023)
Glioblastoma is the most malignant tumor of the central nervous system. Current treatments based on surgery, chemotherapy, radiotherapy, and more recently with selected immunological approaches are unfortunately dismal and less than 2% of patients survive after 5 years. Thus, urgent need for new therapeutic strategies are highly required. Here we report the unprecedented positive results of protection from glioblastoma growth in the animal experimental system after vaccination with the glioblastoma GL261 cells stably expressing the MHC class II transactivator CIITA. Mice injected with GL261-CIITA express de novo MHC class II molecules and reject or strongly retard tumor growth as a consequence of rapid infiltration with CD4+ and CD8+ T cells. Importantly, mice vaccinated with GL261-CIITA cells by injection in the right brain hemisphere strongly reject parental GL261 tumors injected in the opposite brain hemisphere, indicating not only the acquisition of anti-tumor immune memory but also the capacity by immune T cells to migrate within the brain overcoming blood brain barriers. GL261-CIITA cells are a potent anti-gliblastoma vaccine stimulating a protective adaptive anti-tumor immune response in vivo as a consequence of CIITA-driven MHC class II expression and consequent acquisition of surrogate antigen presenting function to tumor-specific CD4+ Th cells. This unprecedented approach for glioblastoma demonstrate the faisibilty of novel immunothereutic strategy to be possibly applied in clinical setting.